Problem Solving in High School Biology: Students’ Agentic Response to Differentiation - Janet English; Jingoo Kang; Tuula Keinonen; Sari Havu-Nuutinen; Kari Sormunen (Science Education International)
Every student comes to science class with unique skills and problem-solving abilities; unfortunately, there is limited research on how to differentiate instruction so that equitable progress can be made for every learner. We used a novel pedagogical approach to differentiate for a wide range of problem-solving abilities when students were learning to solve high school biology problems. Eighty-seven students were given tiered problem sets and asked to choose and solve one of the three differentiated problems; each problem was presentedwith an explicitly different level of difficulty. Using a sequential explanatory mixed-methods approach, we examined which problem students chose to solve, why and how they chose their problem, and how well the student’s choices aligned with their perceived abilities. A majority of students (88%) chose the problem that aligned with their perceived abilities, and the most effective alignment was the problem a little more difficult than they were used to solving. This differentiated approach helped ensure that a wide range of studentabilities received equitable problem-solving experiences regardless of ability. Choice and alignment were important to students’ learning to solve problems.